Pemidanaan terhadap Pelaku Main Hakim Sendiri dalam Kaitannya dengan Kontrol Sosial (Social Controlling) - I Made Khrisna Dwi Payana; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Jurnal Interpretasi Hukum, 2020)
Vigilante (vigilante) creates an outburst of emotions and resentment from the community about the failure of law enforcers to carry out their duties to find criminals. So that it causes mistakes and acts alone without any legal basis and applicable laws. As for the problems found: 1. What is the legal arrangement for vigilante acts? 2. What is the criminal sanction for vigilante actors in relation to social control? The purpose of this research is to find out the qualifications of vigilante one criminal act along with the criminal threat, and it is important that the imposition of vigilante offenders regulate the behavior of the community. This study uses a normative research method, namely legal research which examines various aspects of written law. There is a research finding that the act of vigilantism is due to participation, emotional factors, lack of understanding of the law, the social situation and the law enforcement's inactivity towards the perpetrator is threatened with a criminal act based on the provisions of Article 170 of the Criminal Code.